(untitled) (Ciudades, 2017)
The article proposes a study about the current situation of the public real estate reuse in Italy as an opportunity to activate or drive regeneration processes and urban planning. The survey, by a critical analysis of the application of the regulations and the description of the current state of the public real estate reconversion proceedings, shows that exist a problematic situation, as the enhancement of the public real estate has almost not well included in urban regeneration strategies and in reduction of land use.